2016
DOI: 10.3126/njog.v11i1.16279
|View full text |Cite
|
Sign up to set email alerts
|

Teenage Pregnancy and Obstetric Outcome: A Comparative Study In Urban Nigeria

Abstract: Aims: Teenage pregnancy is a worldwide problem that poses social and health concerns in both industrialized and developing countries. This study therefore sought to evaluate the relevance of age at first pregnancy on obstetric performance.Methods: This was a case control analytical, observational study of teenage women as study group and older control subgroup aged 20-34 years that had their first childbirth between 2009 and 2013 at a mission Hospital in Benin City, South- South, Nigeria. Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
4
4
0
Order By: Relevance
“…[15][16][17][18] In contrary, many studies had showed that adolescent group are more prone to have pre-eclampsia and eclampsia compare to adult group. 7,8,10,12,19 Common pregnancy co-morbidities revealed in this study were, Urinary tract infection 18.4%, similar finding was observed in the study done by Santos et al 20 Lower urinary tract infection was high among younger teenagers and late teenagers, 26.95% and 24.35% respectively compare to adult, which was statistically significant with p=0.01 showed in study done in Romania. 16 However, a study by Nili et al showed only 2% of the teenage pregnancy had developed UTI during pregnancy.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…[15][16][17][18] In contrary, many studies had showed that adolescent group are more prone to have pre-eclampsia and eclampsia compare to adult group. 7,8,10,12,19 Common pregnancy co-morbidities revealed in this study were, Urinary tract infection 18.4%, similar finding was observed in the study done by Santos et al 20 Lower urinary tract infection was high among younger teenagers and late teenagers, 26.95% and 24.35% respectively compare to adult, which was statistically significant with p=0.01 showed in study done in Romania. 16 However, a study by Nili et al showed only 2% of the teenage pregnancy had developed UTI during pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…8 And 92.7% of teenage mothers were married. 7 More than half of teenagers resides 58.6% at rural areas, similar findings was found in study conducted in Bangladesh showed 59.3%. 6 But study conducted in eastern part of Nepal showed that 65% of the teenagers are from urban residents.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations